PENGARUH INTERAKTIVITAS, KEAHLIAN DAN HIBURAN TERHADAP NIAT PEMBELIAN MELALUI SHOPEE LIVE - Kalila, Sekar Ayu; Sadat, Andi Muhammad; Kasofi, Adnan (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
The use of live shopping has increasingly developed as part of the shift in consumer shopping behavior in the digital era. However, in the past two years, there has been a decline in purchases through this feature, particularly on the Shopee Live platform. This condition indicates that the popularity of live shopping has not been fully followed by an increase in consumers’ purchase intention. This study aims to examine the influence of interactivity, streamer expertise, and entertainment on purchase intention in the context of Shopee Live. The research adopts the Stimulus-Organism-Response (SOR) theory to explain how stimulus elements affect consumers’ behavioral responses. Data were collected from 180 respondents who had previously watched Shopee Live in the Jabodetabek area, using purposive sampling. The research instrument was distributed through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS 4 software. The results show that interactivity, streamer expertise, and entertainment have a positive and significant effect on consumers’ purchase intention through Shopee Live.